Pengaruh Model Project Based Learning terhadap Keterampilan Berpikir Kreatif Siswa - Izza, Nur Himmatul Khoiril; Attalina, Syailin Nichla Choirin (Jurnal Simki Pedagogia, 2026)
This study aims to examine the effect of the Project Based Learning model on the creative thinking skills of sixth-grade students at SD Negeri 5 Suwawal. The research employed a quantitative approach with a One Group Pretest-Posttest experimental design. The research subjects consisted of 16 sixth-grade students selected using a saturated sampling technique. The research instrument was an open-ended essay test designed to measure four indicators of creative thinking skills, namely fluency, flexibility, originality, and elaboration. Data analysis involved validity and reliability tests, normality testing, and hypothesis testing using the Paired Sample t-Test. The results indicated an increase in the average score from 61.88 in the pretest to 83.12 in the posttest, with a significance value of 0.000 < 0.05. Improvements were observed across all indicators of creative thinking skills, with the highest increase found in originality. These findings demonstrate that the implementation of the Project Based Learning model has a significant effect on enhancing students’ creative thinking skills. Therefore, this is recommended as an effective instructional model to promote active, meaningful, and creativity-oriented learning in elementary schools.